Effect of ethical ideologies on ethical judgment of future accountants: Malaysian evidence - Ismail, Suhaiza (Emerald Group Publishing Limited, 2014)
Purpose: The objective of this paper is to investigate the effect of ethical ideologies on ethical judgments of future Malaysian accountants in general situations and based on the legality of the situations. The examination covers the relationships of both the specific ethical dimension (i.e. idealism and relativism) and the specific categories of ideology (i.e. absolutist and subjectivist) on ethical judgments. Methodology: Using a survey questionnaire comprising of the Ethical Position Questionnaire (EPQ) and ethical dilemma vignettes, 396 usable responses were received. In achieving the objectives, multivariate analysis of variance (MANOVA), correlations and univariate analysis of variance (ANOVA) were performed. Findings: The study discovered a significant impact of ethical ideology on judgments regardless of the legality of the cases. In addition, the study found a significant positive and negative impact of idealism and relativism, respectively, on ethical judgment. Moreover, the study reported that absolutists are stricter whilst situationists are more lenient in making ethical judgments compared to other ideologies. Originality/Value: The present study investigated the effect of ethical ideologies on ethical judgment, in general, as well as the effect on ethical judgment based on the legality of the ethical dilemma. This study also considered the effect of the two dimensions of ethical ideology – idealism and relativism – on ethical judgment and captured the four categories of ideology based on the taxonomy of ethical ideologies.